Design of hierarchical SnSe2 for efficient detection of trace NO2 at room temperature. Issue 35 (6th August 2021) - Wang, Tingting; Wang, You; Zheng, Shengliang; Sun, Quan; Wu, Ruozhen; Hao, Juanyuan
Abstract : Nanosheet-assembled hierarchical SnSe2 could serve as a new suitable candidate for high-performance room-temperature NO2 gas sensing. Abstract : Layered tin diselenide (SnSe2 ) has aroused widespread scientific interest by virtue of its exceptional chemical, physical, and electrical characteristics. The distinctive features of SnSe2 enable it to be an ideal candidate for efficient detection of NO2 at room temperature. Herein, hierarchical SnSe2 assembled from thin nanosheets was designed and prepared through a facile solvothermal method. An ultralow detection limit (10 ppb) and considerable NO2 sensing performance were obtained at room temperature. A sensor based on hierarchical SnSe2 demonstrated a high response value of 1200% (triple that of SnSe2 nanosheets) and short response/recovery time of 50/55 s toward 10 ppm NO2 . These remarkable sensing properties are uncommon in two-dimensional (2D) materials at room temperature. Additionally, the sensor exhibited superb selectivity, reliable reproducibility, and excellent long-term stability within 5 months. These enhanced sensing properties could be ascribed to the unique hierarchical structures, which possess large accessible space that enhances the adsorption and diffusion of gas molecules. This study offers a new strategy to improve the sensing performance of SnSe2 through rational morphology and structure design.